Detection and Localization of a Nonpalpable Subdermal Contraceptive Implant Using Ultrasonography: A Case Report - Gurel, Kamil; Gideroglu, Kaan; Topcuoglu, Ata; Gurel, Safiye; Saglam, Ibrahim; Yazar, Sukru (ELSEVIER SINGAPORE PTE LTD, 2012)
Subdermal contraceptive implants should be removed after the maximum duration of action or whenever desired. In some circumstances, such as improper insertion, migration, or fibrosis of the implant, the implant might become nonpalpable and the use of imaging techniques are required to localize and remove it. Ultrasonography with high-frequency transducers is recommended as the first-line method for localization. In this report, the ultrasonographic findings of a nonpalpable implant and the results of ultrasonography-guided skin localization are described. (C) 2012, Elsevier Taiwan LLC and the Chinese Taipei Society of Ultrasound in Medicine.
Keywords: contraceptive device; device removal; ultrasonography